Interpretation of NOTCH3 mutations in the diagnosis of CADASIL - Rutten, Julie W; Haan, Joost; Terwindt, Gisela M; van Duinen, Sjoerd G; Boon, Elles MJ; Lesnik Oberstein, Saskia AJ (Expert review of molecular diagnostics, 2014)
CADASIL is an autosomal dominant inherited disease, characterized by mid-adult onset of cerebrovascular disease and dementia. CADASIL is caused by mutations in the NOTCH3 gene, which encodes the NOTCH3 protein. Pathogenic mutations in CADASIL are highly distinctive in the sense that they lead to the loss or gain of a cysteine residue in 1 of the 34 EGFr domains of the NOTCH3 protein. The majority are missense mutations, but small deletions, insertions and splice-site mutations have been reported, which typically also lead to a numerical cysteine alteration. Whether numerical cysteine-altering mutations are a rule in CADASIL remains subject of debate, as there are reports suggesting pathogenicity of other types of mutations. However, for most of these the association with CADASIL was later revoked or is questionable. Here, we discuss and provide recommendations for the interpretation of NOTCH3 mutations in the diagnosis of CADASIL.